Poligami dan Larangannya dari Perspektif Hadits - Irsyad Nugraha (IJoIS: Indonesian Journal of Islamic Studies, 2021)
This study aims to discuss the hadith about polygamy and its prohibitions. This research method is qualitative with the approach of hadith takhrij and sharah hadith text and content analysis. The results and discussion of this research include general views of polygamy, takhrij of the hadiths about polygamy, hadith sharah and the meaning of hadith about the prohibition of polygamy. The conclusion of the research shows that polygamy has been regulated by Islam and state regulations where takhrij, sharah and the meaning of the hadith text about polygamy can be used as a legal basis as well as the prohibition of polygamy is strictly intended to maintain the status of women.